Water Scarcity in Pakistan: Analyzing Its Political, Social, And Economic Impacts - Dr. Shahida Begum; Ahmed Ali (Indus Journal of Social Sciences, 2025)
Water shortage problems of Pakistan are now a matter of national concern due to their impact on socioeconomic structure and economic development of the nation. This study analyzes the effects of dearth of water resources on Pakistan through qualitative methodology which includes but is not limited to case studies, policy analysis, interviews, and stakeholder analysis. The research delves into the conflicts over interprovincial water distributions, particularly Sindh and Punjab, which has been worsened due to poor governance, institutional silos, and lack of proper policies. The most concerning aspects of water shortage are unsustainability induced by climate change, urbanization and agricultural negligence, poor management of aquifers and alteration of ground water levels in conjunction to altered climate policies. The study stresses importance of IWRM, building climate adaptive assets, collaboration in water sharing agreements with focus on Indo-Pak waters treaty. The study highlights gender-specific effects, showing how women and marginalized groups disproportionately carry the weight of water collection. Policy suggestions involve bolstering the Indus River System Authority (IRSA), improving community-focused water management, and implementing smart irrigation techniques to address food insecurity, hydropower shortages, and rural-to-urban migration. The research indicates that in the absence of institutional changes, fair water allocation, and enduring conservation methods, Pakistan’s water security emergency will worsen, endangering lasting socio-economic stability.